Passive control potentials of trees and on-street parked cars in reduction of air pollution exposure in urban street canyons. (September 2015) - Abhijith, K.V.; Gokhale, Sharad
Abstract: This study investigates the passive-control-potentials of trees and on-street parked cars on pedestrian exposure to air pollutants in a street canyon using three-dimensional CFD. Since, according to some studies trees deteriorate air quality and cars parked roadside improve it, the combine as well as separate effects of trees and on-street parked cars have been examined. For this, different tree canopy layouts and parking configurations have been developed and pedestrian exposure for each has been analysed. The results showed, for example, tree crown with high porosity and low-stand density in combination with parallel or perpendicular car parking reduced the pedestrian exposure considerably. Highlights: Trees and on-street parked cars can manipulate pollutant levels in street canyons. Low stand density trees with 0° or 90° car parking reduce pedestrian exposure. Trees with medium crown, high porosity, low stand density reduce pollutant levels. Abstract : This study investigated the combination of trees and on-street parked cars to manipulate pollutant levels in urban street canyons to reduce pedestrian exposure.